2003
DOI: 10.1172/jci200318114
|View full text |Cite
|
Sign up to set email alerts
|

The Fgl2/fibroleukin prothrombinase contributes to immunologically mediated thrombosis in experimental and human viral hepatitis

Abstract: contributed equally to this work. Conflict of interest:The authors have declared that no conflict of interest exists. Nonstandard abbreviations used: tissue factor (TF); murine hepatitis virus type 3 (MHV-3); postcoitus (pc); alanine aminotransferase (ALT); hepatitis B surface antigen (HBsAg); hepatitis B e-antigen (HBeAg); hepatitis B viral capsid (HBcAg); severe acute respiratory syndrome (SARS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
132
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(142 citation statements)
references
References 39 publications
(52 reference statements)
10
132
0
Order By: Relevance
“…Recently, Levy and coworkers (34) reported their independent generation of Fgl2-deficient mice and provided evidence that those animals are indeed less susceptible to mouse hepatitis virus-mediated pathology. They also reported that cells from Fgl2-deficient mice are impaired in their capacity to stimulate coagulant activity on infection by mouse hepatitis virus, although coagulant activity was induced to WT levels in response to endotoxin (34). In combination with our findings, those studies raise the interesting possibility that Fgl2 contributes to pathologically significant coagulative responses under certain conditions but does not critically contribute to protective coagulative responses during type 1 immunity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recently, Levy and coworkers (34) reported their independent generation of Fgl2-deficient mice and provided evidence that those animals are indeed less susceptible to mouse hepatitis virus-mediated pathology. They also reported that cells from Fgl2-deficient mice are impaired in their capacity to stimulate coagulant activity on infection by mouse hepatitis virus, although coagulant activity was induced to WT levels in response to endotoxin (34). In combination with our findings, those studies raise the interesting possibility that Fgl2 contributes to pathologically significant coagulative responses under certain conditions but does not critically contribute to protective coagulative responses during type 1 immunity.…”
Section: Discussionsupporting
confidence: 80%
“…In striking contrast, our analyses of Ͼ500 offspring reveal no significant deficiency in the birth of Fgl2-deficient mice. Although the reason for this discrepancy is unclear, we note that the mice produced by Levy and colleagues contain a LacZ insertion (34). Thus, it is formally possible that forced expression of ␤-galactosidase during embryogenesis could lead to the premature death of their Fgl2-deficient mice.…”
Section: Discussionmentioning
confidence: 90%
“…21,35,36 The results of this study clearly demonstrate that FGL2 is an important effector cytokine of Tregs that contributes to host susceptibility to MHV3-induced FH. Because we have shown that patients with FH and chronic HBV and hepatitis C virus infection have increased levels of FGL2, 30,37 the data presented here in concert with human studies suggest that measurement of FGL2 levels in the plasma may be useful in predicting the outcome of both experimental and human viral hepatitis and may provide a rationale for targeting FGL2 for the treatment of patients with acute and chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 65%
“…30 The lack of effect of macrophages might be attributable to the fact that insufficient cell numbers of fgl2 ϩ/ϩ PEMs were transferred into fgl2 Ϫ/Ϫ mice to recapitulate the endogenous production of FGL2 by liverresident reticuloendothelial cells. It should be noted that macrophages from A/J mice can produce FGL2 to interferon gamma in vitro, yet do not generate FGL2 to MHV-3 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In support of its role as a coagulant are the observation that neutralizing Abs to mfgl2 prevent both fibrin deposition and death from MHV-3 infection (20). Recent studies have also shown that inhibition of reticuloendothelial cell mfgl2 expression through the use of gene-targeted fgl2-deficient (fgl2 Ϫ/Ϫ ) mice results in the prevention of MHV-3-induced fibrin deposition, liver injury, and death (7). Furthermore, we have recently reported that murine and human fgl2 prothrombinase/fibroleukin are highly expressed in endothelium, macrophages, and lymphocytes in xenograft rejection (4).…”
Section: Discussionmentioning
confidence: 99%